Concept of independence, deportations and colonization of Baltic countries (1940–1991) - Strods, Heinrihs (Genocidas ir rezistencija, 2008)
The occupation and annexation of the Baltic states by force in 1940, 1944–1945, and the tragic consequences of these international crimes, led to a revival of the idea of independence, and this idea became dominant in the Baltic nations. The Baltic peoples were persecuted by the Bolsheviks along national and social lines, by the Nazis along racial lines, and then again by the Bolsheviks along social and national lines, thus destroying not only the democratic, political, economic and cultural structure of the Baltic nations, but also the elite of politics, economics and culture that they had built up for centuries. These events have shown that the only way for the Baltic nations to liberate themselves is to get rid of the occupiers and regain their independence. The Kremlin used various forms of ideological, political and spiritual pressure to prevent the idea of independence from manifesting itself in resistance (armed and unarmed), to prevent attempts to weaken Moscow’s influence by increasing economic and cultural autonomy, and to prevent hostility towards the Russian colonisers from becoming a permanent feature of political life in the Baltics.